Limit state design of cantilever retaining walls - Lee, Yuen Hoah. (2009)
The objectives of this project were to discuss the application of limit state design (LSD) method to the design of cantilever retaining walls and the differences between LSD and the overall factor of safety method ( OFS). Some factors affecting the design of cantilever retaining walls were also studied. It was established that the compatibility between the deformation and the corresponding earth pressures was an important factor affecting the design. Two hypothetical problems in the design of cantilever sheetpile walls had been selected for this study. Analysis and design were carried out in accordance with methods recommended by BS8002, EC7 (LSD approaches), and CP2, USS (OFS approaches). Results of analysis were compared among the various design codes in terms of bending moments, required wall embedment depth, and lateral wall displacements. Wherever applicable, wall frictional components had been considered in order to produce a more realistic design. Results calculated by limit equilibrium methods had been compared with results from the finite element analysis to achieve a better understanding of the importance of setting deformation criterion. It was proven that Limit State Designs could produce a more logical design as compared to the conventional overall factor of safety methods.